Основний сюжет на пекторалі з Товстої Могили - Русяєва, М.В. (Археологія, 1992)
Стаття присвячена новій інтерпретації головної сцени пекторалі у взаємозв'язку з історією і культурою Боспору, де вона була виготовлена. В статье дается новая интерпретация двух центральных мужских фигур на золотой пекторали из Толстой Могилы. Рассмотрены разнообразные точки зрения ученых относительно их семантического значения. Приводятся доказательства их связи с дионисийским культом на Боспоре. Сравнительно-стилистический анализ двух персонажей, сопоставление пекторалей из Большой Близницы и Толстой Могилы, широкое применение шкуры в дионисийских ритуалах, существование тесных контактов между боспорскими царями и Скифией в 1-й половине IV в. до н. э. и ряд других данных позволяют считать, что на пекторали из кургана Толстая Могила изображены два царя: боспорский и скифский — возможно, Левкои I и Атей или его соправитель перед посвящением последнего в дионисийские таинства. The article presents the new interpretation of two central male figures on the gold pectoral from the Tolstaya Mogila (Thick Grave) burial mound. Expositions of various scholars
concerning their semantic meaning are considered. Evidence is furnished to demonstrate their connection to the Dionysus cult on Bosporus. The comparative stylistic analysis of the characters, the comparison of pectorals from the Bolshaya Bliznitsa and Tolstaya Mogila burial mounds, wide use of skin in Dionysus rituals, close contacts existed between Bosporus kings and Scythia in the I half of the IV century B.C.— these and some other data enable us to consider the two kings depicted on the pectoral from the Tolstaya Mogila burial mound to be the Bosporus king and the Scythian king — maybe, Levkon I and Athey or his co-ruler before initiating the latter to the Dionysus sacraments.